Simulation of photovoltaic installation connected to the grid with storage system. (December 2017) - Mabrouk, S. Ben; Oueslati, H.; Mabrouk, A. Ben; Zizzo, G.; La Cascia, D.; Dusonchet, L.; Favuzza, S.; Massaro, F.
Abstract: In the present paper, a new approach for the management of energy resources in a research laboratory is proposed and evaluated. A simulation study for the photovoltaic (PV) installation was conducted under the Tunisian-Italian cooperation project DE.DU.ENER.T, using renewable energy and economic criteria. The aim of the study is to improve the energy efficiency in order to minimize the electricity cost consumed in the laboratory. A Hybrid Renewable Energy System consisting of a photovoltaic field of 12KWc was installed to reduce the exorbitant bills, due to intensive energy equipment such as drying ovens and workstations, using sustainable, green and clean sources. In addition, a sizing theoretical study of the PV system was primarily realized in order to evaluate, in the first hand, the compatibility between different equipment and to compare, in the second hand, with results given by two software SMA Sunny Design and PV*SOL. We designed and managed these systems optimally to promote the self-consumption of the electric energy in the LPT Research laboratory building. The focus would be on the use of the PV system by evaluating the impacts of electricity generation using renewable energy levied on electricity grid (energy injection and extraction) and the economies that can be achieved during operating hours. Results of PV-SYST study obtained by the simulation of our installation will be discussed.